WAYS OF PURIFICATION OF EXTRACTS OBTAINED FROM WILD PLANT RAW MATERIAL OF THE SIBERIAN FEDERAL DISTRICT - Dyshlyuk L.S.; Kashirskich E.V.; Noskova S.Y.; Piskaeva A.I.; Izgaryshev A.V.; Garmashov S.Y. (Техника и технология пищевых производств)
It is known that the excess of maximum permissible concentrations of harmful substances is observed in the Siberian Federal District. This is a cause of their accumulation in the body which results in health problems and lowering the quality of life. Wild plant raw material is a rich source of alkaloids, glycosides, coumarins, vitamins, essential oils, phenols and other groups of nutrients that provide recovering and protective action. The most promising method of extraction of bioactive compounds from wild plant raw material is extraction leading to obtaining galenicals and neogalenicals. The most important step in extraction of biologically active compounds is purification of extracts from the ballast substances. The paper deals with four ways to purify extracts obtained from wild plant raw material of the Siberian Federal District. The most effective way for purification of extracts has been founded. It is a two-step purification (ultrafiltration and reversed-phase liquid chromatography) which allows us to achieve the quality values of extracts purification from the ballast substances in the range of 77.7-95.4%.The technological scheme of extract production from wild plant raw material of the Siberian Federal District (cowberry ( Vaccinium vitisidaeva L .) leaves, viburnum fruits ( Viburnum opulus ), sea buckthorn fruits ( Hippophae rhamnoides ), echinated hips ( Rosa acicularis ), mountain ash fruits ( Sorbus aucuparia ) has been developed. The main technological steps of extract production are preparation of wild plant raw materials; preparation of the extractant or a mixture of extractants; obtaining of extracts; concentration; purification of extracts; crude product obtaining; purification of a crude product; standardization for active ingredients; packing, labeling, prepackaging of finished products.